A review of mycotoxin biosynthetic pathways: associated genes and their expressions under the influence of climatic factors. (September 2021) - Kolawole, Oluwatobi; Meneely, Julie; Petchkongkaew, Awanwee; Elliott, Christopher
Abstract: Fungal contamination of agricultural commodities, particularly by mycotoxigenic fungi, represents an enormous concern for global food security in terms of feeding the world's growing population with sufficient and safe food. Not only do they reduce crop yield and quality, but they also produce substantial numbers of mycotoxins, which pose serious adverse health effects in human and animals. As the genome of most mycotoxigenic species have been sequenced, the gene clusters involved in the biosynthesis of agriculturally important mycotoxins including aflatoxins, fumonisins, ochratoxins, zearalenone and trichothecenes, have been largely identified and characterised, with their roles elucidated by researchers. This review provides a comprehensive overview of the current knowledge of genes involved in the biosynthetic pathways of mycotoxins. In addition, the influence of climatic factors including water, temperature and carbon dioxide on differential mycotoxin gene expressions have been highlighted. Overall, the relationship between the relative expression of key regulatory and structural genes under different environmental conditions is significantly correlated with mycotoxins production. This indicates that mycotoxin gene induction can be used as a reliable indicator or marker to monitor mycotoxin production pre-and-post harvest. Furthermore, current strategies to manage mycotoxin risks still require improvement. Thus, an accurate understanding of the molecular mechanisms of mycotoxin biosynthesis in mycotoxigenic species could help to develop an innovative, robust targeted control strategy. This could include the exploitation of novel compounds, which can inhibit biosynthetic genes, to minimise mycotoxin risks.